A STUDY OF DRUG-DRUG INTERACTIONS AMONG PATIENTS RECEIVING MULTIDRUG THERAPY IN THE INTERNAL MEDICINE UNIT (Journal of Medical & Health Sciences Review, 2025)
Background: Drug-drug interactions (DDIs) are a significant but often under-recognized cause of adverse drug events, particularly in hospitalized patients receiving multidrug therapy.Objective: To evaluate the prevalence, severity, and patterns of drug-drug interactions among hospitalized patients receiving multidrug therapy and to identify factors associated with increased DDI risk. Methods: This descriptive, cross-sectional study was conducted at Tertiary Care Hospital ,Karachi from 1st December 2024 to 10  May 2025. A total of 235 patients were included in the study. Data were collected using a structured proforma designed to capture demographic information, clinical diagnosis, prescribed medications, and duration of hospital stay. Prescriptions were manually reviewed to identify all concurrent medications, and drug interaction screening was carried out using trusted, evidence-based drug interaction checkers.Results: Out of 235 patients, 184 (78.3%) had at least one potential DDI, with a total of 527 interactions identified. Moderate interactions accounted for 40.2%, minor for 30.9%, and major for 28.9%. A statistically significant association was found between the number of prescribed drugs and the presence of DDIs (p < 0.001). Older age (≥65 years) and multiple comorbidities were also significantly associated with a higher frequency and severity of interactions.Conclusion: It is concluded that DDIs are highly prevalent among patients on multidrug therapy, especially in older adults and those with polypharmacy.